Characteristics of Siblings with Familial Mediterranean Fever: A Single-Center Experience - Elif Arslanoglu Aydin; Esra Baglan; İlknur Bagrul; Emine Nur Sunar Yayla; Nesibe Gokce Kocamaz; Semanur Ozdel (Turkish Archives of Pediatrics)
Objective: Familial Mediterranean fever (FMF) is a hereditary, autoinflammatory disease. The characteristics of siblings with FMF have not been described in large cohorts up to now. This study aimed to examine the features of siblings with FMF.